Acesso e permanência de alunos de engenharia da UTFPR - Câmpus Medianeira - Gómez, Magela Reny Fonticiella [UNESP] (2015)
This work consists in a research of bibliographic and documental nature, that aimed to to evaluate the admission, the permanency and the consequent evasion, focusing specifically on the Engineering superior courses of UTFPR Câmpus Medianeira. The university's history was rescued and also the involved courses, since its beginning and the Brazilian reality was discussed as a way to contextualize the problem. Statistical data about the school evasion in the Brazilian Higher Education were collected, seeking to relate them with the indicators of the Universidade Tecnológica Federal do Paraná and the Câmpus Medianeira. The raised and analyzed factors were investigated by the academic system information about the statistical data of permanency and evasion features. A very expressive factor was to find how the geographic mobility happens in the country and in the region where the IES investigated is located, considering that it is adopted the process of candidate selection (access) to the courses with the ENEM average by the SiSU process. A very expressive factor was to verify how the geographical mobility of these students in the country and in the region where the IES investigated is located, once the process of candidate selection (access) is adopted to the courses with the ENEM's grade by the SiSU process. An increasing bias for the access to the Higher Education occurs due to the increasing of the vacancy in IFES and to the high students' mobility enabled by the SISU. The data analysis was performed from the information categorization, showing the evasion reasons. It was verified that the evasion rates have fallen since the course consolidation and, mainly, because of the public policies implanted. Therefore, strategies and affirmative actions need to be effectively incremented and enlarged to guarantee the permanency of these students in the university, creating mechanisms that ensure their course's conclusion.